Flow through reactors for organic chemistry: directly electrically heated tubular mini reactors as an enabling technology for organic synthesis - Kunz, Ulrich; Turek, Thomas (Beilstein Journal of Organic Chemistry, 2009)
Until recently traditional heating in organic chemistry has been done with oil heating baths or using electric heat exchangers. With the advent of microwave equipment, heating by microwaves was rapidly introduced as standard method in organic chemistry laboratories, mainly because of the convenient possibility to operate at high temperature accompanied by accelerated reaction rates. In the present contribution we discuss the method of heating small, continuously operated reactors by passing electric current directly through the reactor wall as an enabling technology in organic chemistry. The benefit of this method is that the heat is generated directly inside the reactor wall. By this means high heating rates comparable to microwave ovens can be reached but at much lower cost for the equipment. A tool for the comparison of microwave heating and traditional heating is provided. As an example kinetic data for the acid catalyzed hydrolysis of methyl formate were measured using this heating concept. The reaction is not only a suitable model but also one of industrial importance since this is the main production process for formic acid.
Keywords: direct electric heating; flow reactors; micro reactors; organic chemistry; reaction kinetics

Microreactors – New Technology for Modern Chemistry - Ehrfeld, W.; Hessel, V.; Löwe, H. (Wiley-VCH, 2000)

(untitled) - Schmalz, D.; Häberl, M.; Oldenburg, N.; Grund, M.; Muntermacher, H.; Kunz, U. (Chem. Ing. Tech., 2005)

(untitled) - Kirschning, A. (Beilstein J. Org. Chem., 2009)

(untitled) - Wiles, C.; Hammond, M. J.; Watts, P. (Beilstein J. Org. Chem., 2009)

(untitled) - Palmieri, A.; Ley, S. V.; Polyzos, A.; Ladlow, M.; Baxendale, I. R. (Beilstein J. Org. Chem., 2009)

(untitled) - Mak, X. Y.; Laurino, P.; Seeberger, P. H. (Beilstein J. Org. Chem., 2009)

Practical Microwave Synthesis for Organic Chemists - Kappe, O. C.; Dallinger, D.; Murphree, S. (Wiley-VCH, 2008)

(untitled) - Cecilia, R.; Kunz, U.; Turek, T. (Chem. Eng. Process., 2007)

(untitled) - Menneke, K.; Cecilia, R.; Glasnov, T. N.; Gruhl, S.; Vogt, C.; Feldhoff, A.; LarrubiaVargas, M. A.; Kappe, O. C.; Kunz, U.; Kirschning, A. (Adv. Synth. Catal., 2008)

(untitled) - Ceylan, S.; Friese, C.; Lammel, C.; Mazac, K.; Kirschning, A. (Angew. Chem., 2008)

(untitled) - Kurano, M. (Direct heating tube and method of heating fluid using the same, 2006)

(untitled) - Warren, H. M.; Hayworth, W. R.; Hawthorne, M. S. (Resistive film on alumina tube, 2006)

(untitled) - Schubert, K.; Brandner, J. (Wärmeübertragung auf ein Fluid in einem Mikrostrukturkörper, 1999)

(untitled) - Schubert, K.; Brandner, J. (Microstructured apparatus for heating a fluid, 2004)

International Conference on Microwave and Flow Chemistry - Kunz, U.; Turek, T. (Antigua, 2009)

Polymers as aids in organic chemistry - Mathur, N. K.; Narang, C. K.; Williams, R. E. (Academic Press, 1980)

Synthesis and separation using functional polymers - Sherrington, D. C.; Hodge, P. (John Wiley and Sons, 1988)

(untitled) - Kirschning, A.; Altwicker, C.; Dräger, G.; Harders, J.; Hoffmann, N.; Hoffmann, U.; Schönfeld, H.; Solodenko, W.; Kunz, U. (Angew. Chem., Int. Ed., 2001)

(untitled) - Kunz, U.; Schönfeld, H.; Kirschning, A.; Solodenko, W. (J. Chromatogr., A, 2003)

(untitled) - Schönfeld, H.; Hunger, K.; Cecilia, R.; Kunz, U. (Chem. Eng. J., 2004)

(untitled) - Solodenko, W.; Wen, H.; Leue, S.; Stuhlmann, F.; Sourkouni-Argirusi, G.; Jas, G.; Schönfeld, H.; Kunz, U.; Kirschning, A. (Eur. J. Org. Chem., 2004)

(untitled) - Kunz, U.; Kirschning, A.; Wen, H.-L.; Solodenko, W.; Cecilia, R.; Kappe, C. O.; Turek, T. (Catal. Today, 2005)

(untitled) - Michrowska, A.; Mennecke, K.; Kunz, U.; Kirschning, A.; Grela, K. (J. Am. Chem. Soc., 2006)

Green Separation Processes: Fundamentals and Applications - Jas, G.; Kunz, U.; Schmalz, D. (Wiley-VCH, 2005)

(untitled) - Kirschning, A.; Solodenko, W.; Mennecke, K. (Chem.–Eur. J., 2006)